A Case of Statin-Associated Autoimmune Myopathy: Management and Treatment - Mercedes Malone; Abdelilah Lahmar; Atif Siddique; Michael Rozboril; Jesse L. Kresak (SAGE Publishing, 2023)
Elevated lipid panels are associated with an increased risk of cardiovascular disease. Management of heart disease with lipid lowering agents play a vital role in medicine. Statins are one group of medications that are widely utilized in the medical field to decrease the risk of atherosclerotic disease. Statins work by inhibiting the hepatic enzyme 3-hydroxy-3-methylglutaryl-coenzyme A reductase (HMGCR). Although statins are one of the most effective drugs for secondary and primary prevention of heart disease, they are not without risks and side effects such as hepatotoxicity and myopathy. We present a case of a male patient who developed progressively worsening muscle weakness and elevated muscle enzyme markers upon initiation of a statin. His symptoms persisted despite a trial of an alternative statin and subsequent discontinuation of all statin medications. A multitude of possible etiologies were considered and ranged from infectious, autoimmune, cancerous, to congenital in nature. Environmental factors, such as exposure to medications or toxins, were also considered as one of the possible precipitating factors. The association between his statin consumption and muscle weakness were not easily apparent at first. He required further workup including physical examination, electromyography, panel of myositis antibodies, and muscle biopsy. After clinical suspicion and elevated antibodies to HMGCR beyond the normal limit, he was discovered to have statin-associated autoimmune myopathy. The patient improved with the treatment of immunosuppressive agent's prednisone and methotrexate.